MINAT NASABAH MUSLIM DAN NON-MUSLIM MENYARANKAN ORANG LAIN MENJADI NASABAH BANK SYARIAH (Studi Kasus Bank Syariah di Denpasar, Bali) - Rizal Yaya; H. Hilda (Universitas Trunojoyo Madura, 2015)
The purpose of this study is to assessthe willingness of muslim and non-muslim customers to advise others to become the customers of Islamic bank. A hundred fifty customers from various religion background, participated in the survey undertaken in an Islamic bank in Denpasar. The descriptive statistics showsthat 55.33% of the respondents agreed or strongly agreed to advise others to become the customers of Islamic banks, 0.67% disagreed or strongly disagreed and 44% neither agreed nor disagreed. Among non-Muslim customers, 61.25% agreed or strongly agreed to advise Muslims to become the customers of Islamic banks and 32.50% agreed or strongly agreed to advise other non-Muslims to become the customers of Islamic bank. Statistically, there is no different perception in advising others to become the customers of Islamic banks,between Muslim and non-Muslim respondents. Separate interviews with some Muslims and non-Muslims customers suggested that the universality of Islamic bank mechanism and their convenience in dealing with the Islamic bank were reasons to advise Muslim and non-Muslim to become the customers of Islamic bank.These findings refuse the claim of Satyagraha Movement promoted by an academician, Wedakarna, that Islamic bank is not suitable for Hindu people who are majority in Bali.